Assessment of the cognitive functions in kayakers of the national team after a training cycle combined with whole body cryotherapy - Augustyńska, Beata; Żyła, Magdalena; Rakowski, Andrzej; Szark-Eckardt, Mirosława; Mrozkowiak, Mirosław; Łubkowska, Wioletta (Medical and Biological Sciences, 2016)
Introduction. Using the Quick Mind Testing method, the efficiency of cognitive functions in kayakers after physical training combined with whole body cryotherapy was assessed. Material and methods. The athletes (n = 17) performed the Quick Mind Testing on the first day and at the end of a 2-month training cycle, as well as before and after whole body cryotherapy conducted between the 5th and the 15th day of the cycle. Cryotherapy was administered twice a day, before and after training (20 sessions altogether). One cryotherapy session lasted 3 mins with the temperature gradually decreased from the initial -120oC to the final -145oC. Results. After the training period, the kayakers committed approx. 2 times less incorrect Go and NoGo reactions, and approx. 12% more correct NoGo (p < .004) reactions, as well as gave more correct answers in the ATTENTION test (p < .004) than on the first day of training. After cryotherapy, as compared with the results obtained before the cryochamber stimulation, the kayakers gave more correct answers in the ATTENTION test. Conclusions. Physical training combined with whole body cryotherapy increases the mental efficiency of kayakers, which may affect the efficiency of physical exercise.